Microencapsulatin of thyme oil by coacervation - Martins, I.M. (2010)
The objective of this work is to develop a novel coacervation process to produce microcapsules of polylactide (PLA) to encapsulate thyme oil that will be used in cosmetics. The novelty of this approach consists of dissolving PLA in dimethylformamide (DMF) which is a good solvent for PLA but in addition has high solubility in water. Upon contact with water, the homogeneous solution of PLA in DMF promotes the precipitation of PLA around the thyme oil core. The produced microcapsules have bimodal particle size distributions in volume with a mean particle size of 40 mm. Microcapsules analysis by microscopy have confirmed the spherical shape, the rough surface and allowed the estimation of the wall thickness around 5 mm. Quantification of the encapsulated thyme oil was performed by gas chromatography and allowed to evaluate the quality of the encapsulated oil and pointed out for a preferential encapsulation of thyme oil apolar compounds.